GH Replacement in the Elderly: Is It Worth It? - Ricci Bitti, Silvia; Franco, Marta; Albertelli, Manuela; Gatto, Federico; Vera, Lara; Ferone, Diego; Boschetti, Mara (Frontiers in Endocrinology, 2021)
Growth hormone (GH), once the age of linear growth is completed, continues to play a fundamental role for the human body. In adulthood, GH contributes to regulate muscle, cardiovascular and bone metabolism. The same happens in old age, although there is less data on the effect of GH in the elderly. Regardless the age of onset, a reduced quality of life (QoL), an increased cardiovascular risk and an accelerated age-related decline in physical strength have been demonstrated in the elderly with GH deficiency (EGHD). In adults with GH deficiency (AGHD), recent studies suggest a role of GH replacement therapy (GHrt) in improving lean/fat mass ratio, blood pressure, lipid profile, bone metabolism and QoL. Despite these recent studies, there is still a lack of randomized controlled trials proving these positive effects in EGHD. Moreover, the lack of a long-term positive outcome on mortality, and the cost of GHrt could often impact on treatment decision-making and lead to postpone or avoid the prescription. The aim of this mini-review is to summarize the available data on GHrt in EGHD, in order to highlight its weaknesses and strengths and to provide directions to clinicians that will help in the management of this specific set of patients.